The Effect Of Motivation, Organizational Culture, Work Environment, And Discipline On The Performance Of Employees At The Afiat Clinic, Pmi Hospital, Bogor - Heirunissa, Heirunissa (JMB : Jurnal Manajemen dan Bisnis, 2025)
An employee's performance in a company can experience a decline which results in a decline in the quality of work produced. It can be seen from the lack of a good culture in communicating among employees, the instability of the output results provided by employees, and the lack of employee participation in the organizational culture held/implemented by management at the Afiat Clinic, PMI Hospital, Bogor. The purpose of this study was to analyze the influence of motivation, organizational culture, work environment, and discipline at the Afiat Clinic, PMI Hospital, Bogor. This type of research uses a quantitative approach and data collection in the form of respondent perceptions using a questionnaire. The number of samples used was 75 employee respondents with sample selection using the Purposive Sampling method. Data analysis used in this study used multiple linear regression with the help of the SPSS 26 application. The classical assumption tests used were the normality test, multicollinearity test, and heteroscedasticity test. While the hypothesis test was carried out using the F-test, T-test and coefficient of determination. The results of this study indicate that simultaneously motivation, organizational culture, work environment, and discipline influence employee performance at the Afiat Clinic, PMI Hospital, Bogor. Motivation, work environment, and discipline have a significant effect on employee performance at the Afiat Clinic, PMI Hospital, Bogor, while organizational culture partially has no significant effect on employee performance at the Afiat Clinic, PMI Hospital, Bogor. The results of the determination coefficient calculation show that the influence of motivation, organizational culture, work environment, and discipline on employee performance is 80.4%, while the remaining 19.6% is explained by other variables not included in this research model